If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -4 = 5x + -6 Reorder the terms: -4 + 6x = 5x + -6 Reorder the terms: -4 + 6x = -6 + 5x Solving -4 + 6x = -6 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -4 + 6x + -5x = -6 + 5x + -5x Combine like terms: 6x + -5x = 1x -4 + 1x = -6 + 5x + -5x Combine like terms: 5x + -5x = 0 -4 + 1x = -6 + 0 -4 + 1x = -6 Add '4' to each side of the equation. -4 + 4 + 1x = -6 + 4 Combine like terms: -4 + 4 = 0 0 + 1x = -6 + 4 1x = -6 + 4 Combine like terms: -6 + 4 = -2 1x = -2 Divide each side by '1'. x = -2 Simplifying x = -2
| a/4-5/6=-1/2 | | 19.65-16.6p=-19.45-18.6p-2.6p | | 13y-3=-5y-15 | | 22x+4+120=15x+5 | | x+35+45=180 | | x+7y+2x=18 | | 3x-2=-5+6x | | -11j+4=10j-17 | | 6p-4(3p-9)=-5p+1 | | 3y-11=y | | -5-6x=3x-32 | | -14g=-16g-20 | | 3y-15=-6 | | -17-5k+1=19-10k | | -9+8p=9p | | 18-16=46-8b | | 22x+4-120=15x+5 | | 3a^2+22a+35=0 | | .142(14-7p)-2=-2(.5p+3)+6 | | 7+2x+5x=-42 | | 4.7+3.8=13.2 | | 2m^2-20=2m-60 | | 2m+10=5m | | 5x+7-3x+2=3(2x+6) | | x/2.5=1.4 | | -5x+6=-2x-27 | | 3m-12=-18 | | 5y-30=-15 | | 2y=18+x | | 5(2x-1)+x+12=5x+6(x+2) | | 5d+33=2d | | -9+8=9p |